Novel findings regarding the role of the endocannabinoid system in pediatric functional gastrointestinal disorders - Gisela Chelimsky; Lisa Conant; Pippa Simpson; Liyun Zhang; Serge Marchand; Cecilia Hillard; Thomas Chelimsky (PAIN Reports)
Abstract. Introduction:. Pain constitutes the chief complaint of some functional gastrointestinal disorders (FGIDs). The endocannabinoid (EC) and peroxisome proliferator–activated receptors (PPARs) agonist systems have not been explored as possible contributors. Objective:. To determine if EC and PPAR agonist abnormalities occur in adolescents with FGID. Methods:. Institutional Review Board approved study compared 33 children (12-18 years) with a FGID to 18 healthy controls (HC). Clinical measures: functional disability inventory and pediatric pain questionnaire (PPQ). Endocannabinoid and PPAR agonist concentrations were determined in serum from blood. Data were analyzed using Mann–Whitney and Fisher exact tests (2-sided P < 0.05 considered significant). Results:. When compared to HC, FGID subjects used different terms to describe their pain, which also occurred in more body areas. Functional gastrointestinal disorder subjects exhibited higher palmitoylethanolamide (PEA) and N-oleoylethanolamide, while EC did not differ. Interestingly, PEA correlated significantly with PPQ “worst pain the week before” in the HC group with Spearman ρ = 0.519, P = 0.003, but not in the FGID group (ρ = 0.079, P = 0.66). Conclusion:. Children with FGID exhibit significant pain in nongastrointestinal regions. The higher concentrations of PEA found in the FGID subjects, also occurring in other chronic pain conditions, could reflect a compensatory response due to feedback loops from a downregulated or nonresponsive PPAR system, while the absence of the expected relationship between pain intensity and PEA levels in the FGID group suggests that the PPAR system may not be functioning normally.